The western disturbance of 22 December 1980 - A case study - SHARMA, R. V.; SUBRAMANIAN, D. V. (MAUSAM, 1983)
Rainfall associated with eastward moving westerly systems (WD or induced low) in winter, is normally confined to north of 20 deg. N and moves eastward as the system moves. In a specific case during December 1980 the rainfall activity was observed to extend southward as far as 15 deg. N. Synoptic situation suggests that this is probably due to linkage of a western disturbance with a low pressure area over Arabian Sea. Some features observed on weather charts, satellite and radar pictures during the passage of this system, are presented in this paper.